HUBUNGAN FAKTOR DEMOGRAFI DENGAN BIAS PEMIKIRAN INVESTOR DI PASAR MODAL - Nana Anisa (STIE Perbanas Surabaya, 2012)
This aim study tries to explain about behavior of individual investor that invests funds in capital market. The psychologies of investors affect them to take risk in their infestations. The purpose of this study is to examine the relationship between demographic factors and thinking bias investor in capital markets. The method of data collection in this research is using questionnaires. A questionnaire survey was conducted and responses were obtained from 150 investors from Surabaya. The sampling technique is judgmental (purposive) sampling and snowball sampling. The data obtained was then analyzed using two statistical techniques, namely One Way ANOVA and Independent T-Test to answer the problem. The result shows that of eight demographic factors (gender, ethnic, age, marital status, education, occupation, family size, spending per month) only occupation factor has significant relationship with thinking bias investor in capital market.